Today’s challenge for teachers to develop wisdom on the level of early childhood education - Płóciennik, Elżbieta (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
The modern world requires completely different teacher’ activity than ever before. Actions should be focused on activating the students self-education and self-development under the teacher’s guidance, what comes down to arranging a favorable conditions for learning process and also to connecting the students experience and wisdom with reflection and knowledge from culture transmission. Such modern and alternative approach is the basis of the Teaching for wisdom concept, which promotes holistic, humanistic and integrated education.